Digital-Based Transformation of Islamic Religious Education Learning from the Perspective of Religious Ethics in the Era of Artificial Intelligence at SMA Muhammadiyah PK Kartasura - Rizki, Siti Yuliani; Maksum, Muh Nur Rochim (Universitas Muhammadiyah Surakarta, 2025)
This study intends to assess the transformation of digital-oriented Islamic Religious Education (IRE) learning in the age of artificial intelligence at Muhammadiyah PK Kartasura High School including digital learning, impact on student interest and engagement, evaluation for IRE-digital-based learning and so forth, as well as the challenges currently faced by digital evaluation and its implications for character education and religiosity.This research uses a descriptive qualitative approach and field research design. Data were obtained by observing the digital IRE teaching and learning process, conducting comprehensive interviews with IRE teachers, and documenting the learning media, digital platforms, and evaluation systems used at the school. The data were analyzed using descriptive interpretative techniques to understand learning practices, religious ethical considerations, and technical challenges in the application of artificial intelligence-based evaluation. The results of the study show that digital-based PAI learning through the use of Smart TVs, PowerPoint presentations, animated videos from YouTube, and creative assignments using the Canva application can encourage student interest, engagement, and participation in the learning process. However, digital-based PAI learning evaluation using the Scholar and E-Dumo applications has not consistently influenced students' academic achievement and character building due to technical limitations, system instability, and the limitations of digital platforms in assessing essay answers and the ethical dimensions of learning. This study provides empirical contributions regarding the transformation of digital-based PAI learning from a religious ethics perspective in the era of artificial intelligence and offers practical value for the development of PAI learning and evaluation that balances technological innovation with Islamic educational values.